2016
DOI: 10.1177/1948550616644300
|View full text |Cite
|
Sign up to set email alerts
|

People as Intuitive Retaliators

Abstract: Two studies explore whether people intuitively approve or rather disapprove of a victim personally retaliating against an offender. Participants in Study 1 were introduced to the case of Ameneh Bahrami, an Iranian woman who had been blinded by a jealous suitor and who was given the opportunity to blind her perpetrator in return. Results show that participants who were instructed to complete a secondary task (cognitive load condition) reacted most positively to Ameneh Bahrami’s decision to retaliate. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Second, punishment may reflect a competitive orientation (in SVO terms): By punishing the transgressor, victims may simply aim at making the transgressor suffer (e.g., Baumeister et al, 1995;Fitness, 2001;Yoshimura, 2007), in line with the idea that people are intuitive retributivists who punish in accordance with the "eye for an eye" principle (Aharoni & Fridlund, 2012;Carlsmith & Darley, 2008; see also Eder et al, 2020;Gollwitzer et al, 2016). Likewise, punishment may aim at denigrating the transgressor, reducing their status/power, or demonstrating self-righteousness (i.e., "moralistic punishment"; Jordan & Rand, 2020;Kurzban et al, 2007;Nelissen, 2008).…”
Section: Punishment As a Post-transgression Responsementioning
confidence: 99%
“…Second, punishment may reflect a competitive orientation (in SVO terms): By punishing the transgressor, victims may simply aim at making the transgressor suffer (e.g., Baumeister et al, 1995;Fitness, 2001;Yoshimura, 2007), in line with the idea that people are intuitive retributivists who punish in accordance with the "eye for an eye" principle (Aharoni & Fridlund, 2012;Carlsmith & Darley, 2008; see also Eder et al, 2020;Gollwitzer et al, 2016). Likewise, punishment may aim at denigrating the transgressor, reducing their status/power, or demonstrating self-righteousness (i.e., "moralistic punishment"; Jordan & Rand, 2020;Kurzban et al, 2007;Nelissen, 2008).…”
Section: Punishment As a Post-transgression Responsementioning
confidence: 99%
“…Revenge is a socially decried response to transgressions often seen as inferior to for giveness (Worthington, 2006). However, people intuitively approve of revenge taken by victims (Gollwitzer et al, 2016) and sometimes revenge may even enable victims to leave transgressions behind (Strelan et al, 2017). As such, do people actually condemn venge ance or rather denounce feeling good about taking revenge?…”
Section: Discussionmentioning
confidence: 99%
“…That being said, people also enjoy stories in which the victim takes effective revenge against the perpetrator (Miller, 1998). In a similar vein, research suggests that people's intuitive affective reaction towards revenge is positive: Participants who learned about a victim's quest for revenge experienced more positive emotions under cognitive load than when weighing the pros and cons of revenge deliberately (Gollwitzer et al, 2016). The question we are addressing here is: Is it the vengeful act itself that is morally condemned, or rather the hedonic pleasure that the victim experiences after committing the vengeful act?…”
mentioning
confidence: 93%
“…First, Need for Cognition, an individual difference measure of cognitive style sometimes used to assess the tendency of individuals to engage in type II processing (Petty et al, 2009) has been found to be negatively associated with punitiveness (Sargent, 2004). Second, punitive reactions become more severe with cognitive load (Gollwitzer et al, 2016; Oswald & Stucki, 2009; van Knippenberg et al., 1999). Since type II processing requires cognitive resources (in particular, working memory capacity) to a much greater extent than type I processing, burdening those resources by inducing cognitive load is commonly used in experiments to inhibit type II processing (Evans & Stanovich, 2013, p. 232).…”
Section: Problemmentioning
confidence: 99%
“…Since type II processing requires cognitive resources (in particular, working memory capacity) to a much greater extent than type I processing, burdening those resources by inducing cognitive load is commonly used in experiments to inhibit type II processing (Evans & Stanovich, 2013, p. 232). Third, punitive reactions become less severe when participants are induced to think more carefully about their decision (Gollwitzer et al, 2016; Oswald & Stucki, 2009) – a manipulation that is thought to increase type II processing effort (Evans & Stanovich, 2013, p. 232).…”
Section: Problemmentioning
confidence: 99%